A survey-based design of a pricing system for psychotherapy - Beat Hulliger; Martin Sterchi (Health Economics Review, 2018)
For admission to statutory health insurance, it is common in Switzerland that health care providers negotiate prices for health care services directly with health insurers. Once they agree upon a price, they must submit the resulting price to the Federal Office of Public Health (FOPH), which can then authorize it. Swiss law requires the prices in health care to be based on empirical data. There has been little research on how to derive such a price for health care from empirical data and which data should be used. Based on a collaboration with psychological psychotherapists in Switzerland, we have designed a pricing system. The empirical basis were two representative surveys: a survey about costs and earnings of psychotherapists, as well as a time-use survey for psychotherapy. This paper shows the methodology followed to establish an empirically based pricing system. The paper may serve as a practical guide for health service providers who want to develop a pricing system. Our approach offers a high degree of freedom because it involves the collection of the data and an explicit modelling phase. At the same time, it might be more resource intensive than other approaches that are based on existing data sources.
Keywords: 330; Survey; Health insurance; Health care pricing; Tariff system; Regulation